2019
DOI: 10.1111/codi.14574
|View full text |Cite
|
Sign up to set email alerts
|

Surgical solutions for refractory J‐pouch inlet obstruction

Abstract: Aim Many surgeons consider total proctectomy with ileal pouch–anal anastomosis as the treatment of choice for patients with medically refractory ulcerative colitis or ulcerative colitis with dysplasia. However, obstruction occurring at the pouch inlet or involving the afferent limb can be refractory to nonoperative or endoscopic management. Historically, these refractory obstructions have usually required resection of the pouch. There is now increasing evidence to suggest that pouch salvage surgery may be feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…All patients retained their pouches after a median follow-up of 36.5 months, concluding that, in patients with obstruction who are refractory to endoscopic or medical treatment, good functional results may be obtained with a pouch salvage procedure. 29…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients retained their pouches after a median follow-up of 36.5 months, concluding that, in patients with obstruction who are refractory to endoscopic or medical treatment, good functional results may be obtained with a pouch salvage procedure. 29…”
Section: Resultsmentioning
confidence: 99%
“…Fumery et al 30 reported their experience with 1 patient with an inlet stricture that failed endoscopic balloon dilation, an excision of the stricture at the prepouch ileum, and reanastomosis to the pouch inlet successfully performed as evaluated after 3 years of follow-up. As mentioned above, all patients in the series from Sellers et al 29 who had inlet strictures that were resected and primarily anastomosed retained their pouches after a median follow-up of 36.5 months.…”
Section: Stricture Resection and Reanastomosismentioning
confidence: 93%
See 2 more Smart Citations
“…The causes of ALS were initially thought to include only a displacement of the pre-pouch ileum posterior to the pouch causing obstructive symptoms; but a more contemporary understanding of ALS has shown a growing number of potential abnormalities of this portion of the bowel, many of which can be difficult to identify on initial evaluation. For example, a fibrotic stricture causing ALS may be easily seen during pouchoscopy, but angulation of the afferent limb due to adhesions or an inappropriate rotation of the small bowel mesentery is sometimes only identified at laparotomy with findings of partial or complete obstruction [18].…”
Section: Etiology and Management Of Pouch Complications Structural Complications Of The Pouch Afferent Limb (Af) Complicationsmentioning
confidence: 99%